“Modish manners” and “decent vice”: Adultery in Byron’s The Waltz: An Apostrophic Hymn - Paterson-Morgan, Emily (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
There is a persistent tendency in Byron scholarship to view the poet’s depictions of sexual activity as symbolic or metaphorical, a vehicle for political satire, social commentary, or attacks on religion. However, Byron’s treatment of sex must sometimes be considered as sex qua sex (or as Byron memorably describes it, “fuff-fuff”). This is particularly true of The Waltz: An Apostrophic Hymn, a poem that deftly transforms the transgressive physicality of the “Voluptuous Waltz” into a codified expression of adulterous desire. This article considers how the theme of adultery, a pervasive and contentious element in contemporary print culture, informs Byron’s treatment of waltzing, investigating the rich array of cultural materials he incorporates into his satirical poem. This recovery of the poet’s subtle topical parodies and subversions allows for a more nuanced appreciation of the full scope of his satirical attacks in this complex and multifaceted poem.